Tribal Consciousness in the Poetry of Ramanika Gupta: रमणिका गुप्ता की कविताओं में आदिवासी चेतना - Yadav, Vijay Singh; Singh, Virendra (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Ramanika Gupta made a significant contribution to Hindi literature as a voice for marginalized communities. She authored several books on tribal life and was a renowned litterateur, social worker, and activist involved in multiple fields, including politics. She made remarkable contributions to feminist discourse and served as the editor of the socially-conscious magazine Yuddharat Aam Aadmi. Her efforts brought labor movements from the coalfields of Hazaribagh, Jharkhand, to national attention through literature. Gupta also served as a member of the Bihar Legislative Assembly and Legislative Council. Literature is a natural expression of life, reflecting its essence. While the extent to which literature influences life may be debatable, it undeniably derives its energy and vitality from life itself. In contemporary times, tribal literature is being extensively written and critically reviewed. Tribals are considered the original inhabitants of this land, forming a unique community. Their civilization and culture, developed in the lap of nature away from urban life, stand out as extraordinary. The lifestyle, customs, music, and dance of tribal communities differ significantly from mainstream society. They hold immense reverence and love for nature, which is the foundation of their existence. Abstract in Hindi Language: रमणिका गुप्ता ने विमर्श के रूप में हिंदी साहित्य में अपना महत्त्वपूर्ण योगदान दिया है।उन्होंने आदिवासी जीवन पर कई पुस्तकें लिखी हैं।वे प्रख्यात साहित्यकार,सामजिक कार्यकत्र्ता,समाजसेवा और राजनीति सहित कई क्षेत्रों से जुड़ी हुई थीं। उन्होंने स्त्री विमर्श पर बेहतरीन काम किया और वह सामाजिक सरोकारों की पत्रिका ‘युद्धरत आम आदमी’ की संपादक भी थीं। उन्होंने झारखंड के हज़ारीबाग के कोयलांचल से मजदूर आंदोलनों को साहित्य के ज़रिये राष्ट्रीय स्तर पर पहुँचाने का काम किया। बिहार विधानसभा और विधान परिषद् में विधायक भी रही। साहित्य जीवन की सहज अभिव्यक्ति हैं। साहित्य जीवन को कितना प्रभावित करता है। यह विचारणीय हो सकता हैं, परंतु साहित्य जीवन से ही ऊर्जा और जीवन-शक्ति प्राप्त करता हैं। यह निर्विवाद हैं। वर्तमान समय में आदिवासी साहित्य काफी मात्रा में लिखा जा रहा है और उसकी समीक्षा भी हो रही है। आदिवासी इस धरती के मूल निवासी हैं। आदिवासी समाज एक विशिष्ट समाज है। नगरीय जीवन से दूर प्रकृति की गोद में उनकी सभ्यता और संस्कृति का विकास हुआ। जो अपने आप में अनोखी बात है। आदिवासियों का रहन-सहन, रीति-रिवाज, संगीत-नृत्य आदि सभ्य समाज से भिन्न है। प्रकृति के प्रति उन्हें अपार श्रद्धा एवं प्रेम है, प्रकृति ही उनके जीवन का आधार है। Keywords: आदिवासी चेतना, दलित, मुख्यधारा, संस्कृति, दलित विमर्श